Conservation of Balinese Cultural Traditions in The Layout of The Tejaprana Resort in Ubud, Bali - S, Alwin Suryono (RUAS, 2024)
This paper aims to reveal the existence of Balinese cultural traditions in the layout of Tejaprana Resort in Ubud, Bali, and its preservation. The design of the site, restaurant, and villas reveals the physical-social-meaning system of Balinese cultural tradition through awareness of sense, purpose, and essence. The site's mass-space layout, which lines up in a south-north orientation and slopes eastward following the site's shape, achieves the meaning of appreciating the balance and harmony of nature. The restaurant architecture, with its hollow roof, upper room, and lower room, adapts to the local environment, preserving the meaning of the three layers of nature (top, middle, and bottom) of the Tri Loka philosophy. The restaurant's architecture's openness to local nature preserves the meaning of appreciating the balance of the natural environment (Manik Ring Cucupu Philosophy).